2018
DOI: 10.29252/arakmu.12.2.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cadmium on the Ultrastructure and Metallothionein Levels in the Liver and Kidneys of Japanese quail

Abstract: Background: The aim of this study was to use Japanese quail as an animal model to evaluate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Cytoplasmic vacuolation and degeneration of hepatocytes have been noticed in cypermethrin http://www.ijt.ir; Volume 12, No 4, July-August 2018 challenged rats. This derives support from the studies of other workers reported similar findings from toxicants treated mammals [4,[11][12][13][14][15][16][17][18][19], birds [20], amphibia [21] and fish [ 22,23]. Few investigators have not observed changes in liver after exposure to chlorpyrifos [24] and FYROL [25].…”
Section: Discussionsupporting
confidence: 75%
“…Cytoplasmic vacuolation and degeneration of hepatocytes have been noticed in cypermethrin http://www.ijt.ir; Volume 12, No 4, July-August 2018 challenged rats. This derives support from the studies of other workers reported similar findings from toxicants treated mammals [4,[11][12][13][14][15][16][17][18][19], birds [20], amphibia [21] and fish [ 22,23]. Few investigators have not observed changes in liver after exposure to chlorpyrifos [24] and FYROL [25].…”
Section: Discussionsupporting
confidence: 75%
“…The liver exposed to cadmium undergoes vesicular fatty degeneration in the hepatic lobules and the shape of the hepatocytes transforms into a ring-like (28). Cadmium inside the hepatocytes causes swelling in both the rough endoplasmic reticulum and mitochondria, the cristae lose, nuclear chromatin presses, the fat drops increase, the liver cells disassociate with each other, and the production of metallic protein (Metallothionein) in the hepatic cells increases (29). The number of lysosomes increases, the endoplasmic reticulum is broken, the nucleus is damaged (30) the cell membrane thickens and the nuclear membrane is destroyed by cadmium (31).Cadmium toxicity damages liver cells, increases secretion of liver enzymes, and decreases concentration of antioxidant enzymes (32).…”
Section: Cadmium Toxicity In Livermentioning
confidence: 99%
“…Capillaries in the renal glomeruli and peritubular blood capillaries are congested (38). Cadmium causes cellular changes, as the mitochondria swell, the cristae lose, the nuclear chromatin is compressed, the number of ribosomes increases, the number of microvilli on the surface of the renal tubule cells decreases, and the production of metallothionein in the kidney cells increases (29). The pores of the fenestrated capillaries in the renal glomeruli close, the nuclear membrane is disturbed, the number of lysosome increases, and finally the cells die (31).…”
Section: Cadmium Toxicity In Kidneysmentioning
confidence: 99%
“…Cadmium, which is one of the most common environmental and occupational metallic toxicants, has also been demonstrated to potentially threaten human health [1][2]. Cadmium is a potent heavy metal carcinogenic to animals [3] and humans [4]. The gonads, ventral prostate, liver and kidney are target sites for cadmium toxicity in rodents [5][6].…”
Section: -Introductionmentioning
confidence: 99%